Nile into Tiber : Egypt in the Roman world : proceedings of the IIIrd International Conference of Isis Studies, Faculty of Archaeology, Leiden University, May 11-14, 2005 - Bricault, Laurent.; Versluys, M. J.; Meyboom, P. G. P. (Religions in the Graeco-Roman World, 2007)
Interest in all kinds of interactions between Egypt and Rome has grown considerably over the last decade. This debate has not only altered our views on the impact of Rome on Alexandria and Egypt but also strongly put to the fore the reverse direction of this cultural interaction: Egyptian influences on the Roman world. It is this topic, Egypt in the Roman World , that was central to the IIIrd International Conference of Isis Studies, held in Leiden in May 2005. This book, a selection of the papers delivered at the conference, gives a clear overview of the debate as it has developed in recent years. In two parts (I. Interpretations of the meaning of Aegyptiaca Romana and II. Understanding the cults of Isis in their local context )preceded by a general introduction it offers a broad perspective on the various aspects of cultural interaction between Egypt and Rome, also by bringing together different research traditions in this field.